2008
DOI: 10.1097/tp.0b013e31816b2602
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of Folic Acid Therapy in Heart Transplant Recipients: Follow-Up Analysis of a Randomized Study

Abstract: Although further studies are needed, it seems reasonable to suggest folate therapy to heart transplant recipients. It is possible that properties other than homocysteine reduction may provide antitumoral benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Thirteen RCTs were conducted in European countries (United Kingdom, Norway, Netherlands, Italy, Germany, Switzerland, and France), 9 were conducted in the Americas (United States, Canada, and Brazil), 4 were conducted in Asia (China, India, and the Philippines), and 1 was conducted in Australia and New Zealand. Another 3 RCTs were conducted in multiple countries across continents, including the Vitamin Intervention for Stroke Prevention (VISP) in 3 countries across 2 continents, the 2 Heart Outcomes Prevention Evaluation (HOPE) studies in 13 countries across 3 continents, and the VITAmins TO Prevent Stroke trial (VITATOPS) in 20 countries across 4 continents (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen RCTs were conducted in European countries (United Kingdom, Norway, Netherlands, Italy, Germany, Switzerland, and France), 9 were conducted in the Americas (United States, Canada, and Brazil), 4 were conducted in Asia (China, India, and the Philippines), and 1 was conducted in Australia and New Zealand. Another 3 RCTs were conducted in multiple countries across continents, including the Vitamin Intervention for Stroke Prevention (VISP) in 3 countries across 2 continents, the 2 Heart Outcomes Prevention Evaluation (HOPE) studies in 13 countries across 3 continents, and the VITAmins TO Prevent Stroke trial (VITATOPS) in 20 countries across 4 continents (Tables and ) …”
Section: Resultsmentioning
confidence: 99%
“… RCTs that reported stroke, CHD, or CVD at baseline among some or all participants were classified as having preexisting stroke, CHD, or CVD, respectively. The RCT conducted among participants with heart transplant was classified as those with preexisting CHD/CVD, whereas the RCT among participants with subclinical atherosclerosis was classified as those without preexisting CVD. …”
Section: Resultsmentioning
confidence: 99%
“…The literature review identified 21 articles for detailed assessment, among which 7 were excluded for lack of data on stroke,11, 27-32 and 1 because it was derived from the same study population as another report (figure 1). 33 Our final analysis included 13 RCTs, enrolling 39,005 individuals 17-19, 34-43.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, seven were excluded since no stroke risk was reported (16)(17)(18)(19)(20)(21)(22) , one was excluded due to small patient pool (23) , three were excluded due to no baseline report for folate and homocysteine (22,24,25) , one was excluded due to high dose of folate (1 mg/d) as control (26) and one was excluded due to duplicate study (27) . The final fourteen RCT enrolled 39 420 patients.…”
Section: Resultsmentioning
confidence: 99%